HUBUNGAN TASYRI’ ISLAM DENGAN UNDANG-UNDANG ROMAWI - Nurkhaerah, Sitti (State Institute of Islamic Studies (IAIN) Palu, 2007)
Before the advent of Islam in Arab, Roman civilization had flourished in many aspects of lives such as in philosophy, art and science. Even, Roma used to be a centre for Christian civilization so that it had given an influence to its neighboring lands in abovementioned aspects. However, in respect to the influence of Roman Constitution on Islamic law, a controversy emerges. Some scholars reject the influence but some support it. How the controversy emerges and what analysis employed by them to reject and to support it. This article elaborates that point. Kata Kunci: Tasyri’ Islam, Undang-Undang Romawi